Design and Development of CARE Visitor Management System - Khoo, Wen Bin; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2023)
Design and Development of CARE Visitor Management System Begun in 2021 Malaysia government officially announced that the education sectors allowed to switch their learning method back to physical. A safer method that controls the contact between the students and the public becomes the first consideration that the education sector should take care of. The CARE Visitor Management System is a system that controls and monitors the visitation of the public in the building which is requested by Stellar International School. With the system, the students’ parents are allowed to enter the school building and pick up the students with a safe and efficient method. The system is developed by using Prototype software processing model. The development of the project will assist Stellar International School to control and manage the visitation of students’ parents and reduce Student-Public Contact during the pandemic period.